Enhanced Carrier Injection Across S/D Contacts in Selenium-Based TMD FETs Using KI and Metal Induced Gap-States Engineering - Kuruva Hemanjaneyulu; Jeevesh Kumar; Utpreksh Patbhaje; Mayank Shrivastava (IEEE Journal of the Electron Devices Society)
Lack of transparent contacts has been a critical bottleneck for the two-dimensional Transition Metal Dichalcogenides (TMDs) Field Effect Transistors (FETs). In the absence of approaches to introduce physical doping without inducing crystal damage, charge transfer-based doping has been widely adopted. This manuscript presents a unique charge transfer doping technique using potassium iodide (KI) solution for Selenium-based TMDs, which resulted in charge transfer/doping near the contact edges; however, unlike earlier reports, it doesn’t affect the channel region in the presence of the dopant (i.e., KI). Density functional theory (DFT) based computations are used to investigate these unique experimental observations. DFT calculations show the formation of unique mid-gap states and doping of the TMD region near the contact edge where both KI and Ni were present, which otherwise was missing in the channel region where only KI was present.